WEB-SERVICE FOR WORKING WITH CLIENTS AND EMPLOYEES OF ADDITIONAL EDUCATION CENTERS - Левченко, Д.; Ковалев, И.; Бирюков, И.; Петров, В.; Плотников, Т.; Матохина, Анна; Щербакова, Наталья (SWorldJournal, 2021)
Our article is about web-service for working with clients and employees of additional education centers. A description of the functionality, interfaces of interaction with various users, as well as scenarios of using service is given. The service was impl